2018
DOI: 10.3892/or.2018.6594
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of ABCG2 against oxidative stress in colorectal cancer and its potential underlying mechanism

Abstract: Colorectal cancer (CRC), one of the most common cancer types worldwide, is associated with a high mortality rate, and oxidative stress and inflammation play a vital role in this malignancy. A previous study by our group indicated that ATP binding cassette subfamily G member 2 (ABCG2) was capable of protecting cells from reactive oxygen species (ROS)‑mediated cell damage and death. In the present study, the role of ABCG2 in CRC was investigated by using clinical samples and cell lines. The levels of oxidative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Intensive researches have been made over the past decades to give insight into the relationship between reactive oxygen species (ROS) and CRC ( 158 160 ). Consistently, Zinkzuk et al in 2019 carried out a study and showed superoxide dismutase was amplified, whereas the activities of catalase, glutathione peroxidase, and glutathione reductase were lower in 50 CRC patients.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Intensive researches have been made over the past decades to give insight into the relationship between reactive oxygen species (ROS) and CRC ( 158 160 ). Consistently, Zinkzuk et al in 2019 carried out a study and showed superoxide dismutase was amplified, whereas the activities of catalase, glutathione peroxidase, and glutathione reductase were lower in 50 CRC patients.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…The association between ABCG2 and tumor characteristics has also been widely reported in various cancer types. ABCG2 was positively correlated with the abnormal activation of NF-κB in breast cancer (41) and matrix metalloproteinase 9 in glioma stem cells (42), but played a protective role against oxidative stress and inflammatory factors in colorectal cancer (43). It was of note that the relationship between the Wnt family and ABC family has been explored (44)(45)(46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress and inflammation play important roles in malignant CRC, and the high expression of ABCG2 in CRC tissue may be a feedback of overoxidation reaction, associated with poor prognosis. A cell culture study showed that downregulation of ABCG2 can inhibit the production of antioxidants, inducing tumor cell growth [15], suggesting that ABCG2 is a potential therapeutic target of CRC. Excessive expression of CYP3A4 is detected in colon tissue [16].…”
Section: Discussionmentioning
confidence: 99%